2019
DOI: 10.1002/hep.30793
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA p53‐Stabilizing and Activating RNA Promotes p53 Signaling by Inhibiting Heterogeneous Nuclear Ribonucleoprotein K deSUMOylation and Suppresses Hepatocellular Carcinoma

Abstract: To identify hepatocellular carcinoma (HCC)‐implicated long noncoding RNAs (lncRNAs), we performed an integrative omics analysis by integrating mRNA and lncRNA expression profiles in HCC tissues. We identified a collection of candidate HCC‐implicated lncRNAs. Among them, we demonstrated that an lncRNA, which is named as p53‐stabilizing and activating RNA (PSTAR), inhibits HCC cell proliferation and tumorigenicity through inducing p53‐mediated cell cycle arrest. We further revealed that PSTAR can bind to heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 35 publications
4
99
0
Order By: Relevance
“…In exploring the specific molecular mechanism of CDK1/CCNB1 in regulating cancer, Zhang et al revealed that CCNB1 could affect the cell cycle and apoptosis of pancreatic cancer cells by regulating p53 signaling pathway (Zhang H. et al, 2018). Qin G et al reported that the p53 signaling pathway may be regulated by multiple genes to affect the development of liver cells (Qin et al, 2019). In addition, KEGG pathway enrichment analysis (Figure 1B) showed that multiple DEGs, including CDK1/CCNB1, were enriched in the p53 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In exploring the specific molecular mechanism of CDK1/CCNB1 in regulating cancer, Zhang et al revealed that CCNB1 could affect the cell cycle and apoptosis of pancreatic cancer cells by regulating p53 signaling pathway (Zhang H. et al, 2018). Qin G et al reported that the p53 signaling pathway may be regulated by multiple genes to affect the development of liver cells (Qin et al, 2019). In addition, KEGG pathway enrichment analysis (Figure 1B) showed that multiple DEGs, including CDK1/CCNB1, were enriched in the p53 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Danhier et al (2010) have reported that CDK1/CyclinB1 inhibitor JNJ-7706621 and aurora kinase combined with paclitaxel can effectively treat transplantable liver cancer and inhibit tumor growth. In addition, studies have shown that CDK1 and CCNB1 have inhibitory effects on p53 signaling pathway as regulatory factors in HCC (Qin et al, 2019). Cell cyclin B1 (CCNB1) is an important cell cycle protein whose abnormal expression plays an important role in regulating cell cycle (Jin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA PRAL facilitates the interaction of p53 with HSP90 thus preventing the binding of p53 with MDM2, leading to the stabilization of p53 and the suppression of HCC growth [73]. Similarly, lncRNA PSTAR physically binds to hnRNP K protein and enhances its SUMOylation, which facilitates the formation of the p53-hnRNP K protein complex, thereby competitively blocking MDM2-dependent p53 protein degradation and inhibiting HCC cell proliferation [111]. 3) LncRNAs HOTAIR is capable of serving as a scaffold to bind with PRC2 and E3 ligase Mex3b simultaneously, facilitating the degradation of PRC2 and promoting HBV-induced HCC progression [112].…”
Section: Protein Interaction and Regulationmentioning
confidence: 99%
“…From the enrichment results of the ChIRP-MS analysis and the SNHG6-related genes identified above, we speculated that SNHG6 may be involved in the metabolic process of CRC by interacting with hnRNP proteins. It was reported that lncRNAs can interact with hnRNP proteins and induce hnRNP to splice and process mRNA in CRC, prostate cancer, and hepatocellular carcinoma (20,45,46). Therefore, we wanted to identify the molecule that was involved with SNHG6 and hnRNP protein complexes in CRC metabolism.…”
Section: The Snhg6/hnrnpa1/pkm Axis Was Found To Be Involved In the Mmentioning
confidence: 99%